ANALISIS TATA CARA PEMUNGUTAN PAJAK REKLAME YANG DITERAPKAN OLEH DINAS PENDAPATAN KABUPATEN NIAS SELATAN - Reaksi Zagoto; Erasma F. Zalogo; Paskalis Dakhi (Balance: Jurnal Riset Manajemen dan Bisnis, 2022)
The collection of billboard taxes has similarities with other tax collections that must meet the provisions that are subjective and objective. The Government of South Nias Regency conducts a billboard tax collection in a very unique way, the billboard tax is levied on the management of business licenses, proof of the repayment of the Billboard Tax is one of the requirements that must be submitted to obtain the original document of the Business License issued by the Licensing Office. Based on the results of the analysis of research data, it can be concluded that in general the billboard tax collection procedures applied by the relevant institutions in South Nias Regency have not been implemented in accordance with the relevant regulations. In its implementation, the procedure for determining the object of the billboard tax is carried out normatively with unclear logic. Related institutions generalize the understanding of Billboards as tax objects without regard to the sorting of the rekelame itself (as objects and not tax objects) as stipulated in various laws in particular, PERBUB NISEL Number 52 of 2012. The South Nias Revenue Office imposes two types of tariffs, namely Rp 225,000 for Business Owners and Rp 3,000,000 tariffs applied to the bodies of the Comnditer Company (CV), the determination of the nominal nominal above is done without clear reference (based on the previous culture although it is actually not in accordance with the laws governing it). To realize good governace in the field of breeding, the South Nias Regency Government needs to take several actions, among others, 1) The need for planning periodic evaluation of the procedure for the implementation of voting so that the obstacles faced can be addressed early. 2) Placing competent employees in their fields who have the ability to understand tax regulations and have a high work commitment. 3) Implementation of the use of certain computer applications in calculating taxes owed.